Frontal sinus obliteration with iliac crest bone grafts: review of 8 cases - Monnazzi, Marcelo [UNESP]; Gabrielli, Marisa [UNESP]; Oliveira, Henrique de[UNESP]; Pereira-filho, Valfrido; Gabrielli, Mario [UNESP]; Vieira, Eduardo Hochuli [UNESP] (MDPI, 2014)
This study evaluated postoperative results of 8 cases of frontal sinus fractures treated by frontal sinus obliteration with autogenous bone from the anterior iliac crest. Patients and methods: The medical charts of patients sequentially treated for frontal sinus fractures by obliteration with autogenous cancellous iliac crest bone in the Oral and Maxillofacial Surgery Division of this institution were reviewed. From those, eight had complete records and adequately described long-term follow-up. All were operated by the same surgical team. Those patients were recalled and independently evaluated by 2 examiners. Radiographs and/or CT scans were available for this evaluation. Associated fractures and complications were noted. The average postoperative follow-up was 7 years, ranging from 3 to 16 years. The main complication was infection. Four patients (50%) had uneventful long-term follow-ups and four (50%) experienced complications requiring reoperation. Based on the studied sample studied the authors conclude that the obliteration with autogenous bone presented a high percentage of complications in this series.
Keywords: Frontal sinus fracture; Maxillofacial trauma; Sinus obliteration